The CRESST dark matter search - Buhler, M; Bucci, C; Cooper, S; von Feilitzsch, F; Hohne, J; Jorgens, V; Loidl, M; Meier, O; Nagel, U; Probst, F; Rulofs, A; Sarsa, M; et al. (1998)
The CRESST (Cryogenic Rare Event Search with Superconducting Thermometers) experiment at the Gran Sasso Laboratory will search for dark matter WIMPs using cryogenic detectors. In the first stage we will use four 262 g sapphire crystals with thresholds of about 0.5 keV. This low threshold gives us sensitivity to WIMP masses below 10 GeV, making CRESST complementary to other dark matter searches. The main installation in Gran Sasso is now complete and we report on the first detector tests.